18 F-Choline PET/mpMRI for Detection of Clinically Significant Prostate Cancer: Part 1. Improved Risk Stratification for MRI-Guided Transrectal Prostate Biopsies - Davenport, Matthew S; Montgomery, Jeffrey S; Kunju, Lakshmi Priya; Siddiqui, Javed; Shankar, Prasad R; Rajendiran, Thekkelnaycke; Shao, Xia; Lee, Eunjee; Denton, Brian; Barnett, Christine; Piert, Morand (The Journal of nuclear medicine (1978), 2020)
A prospective single-arm clinical trial was conducted to determine whether F-choline PET/mpMRI can improve the specificity of multiparametric MRI (mpMRI) of the prostate for Gleason ≥ 3+4 prostate cancer. Before targeted and systematic prostate biopsy, mpMRI and F-choline PET/CT were performed on 56 evaluable subjects with 90 Likert score 3-5 mpMRI target lesions, using a F-choline target-to-background ratio of greater than 1.58 to indicate a positive F-choline result. Prostate biopsies were performed after registration of real-time transrectal ultrasound with T2-weighted MRI. A mixed-effects logistic regression was applied to measure the performance of mpMRI (based on prospective Likert and retrospective Prostate Imaging Reporting and Data System, version 2 [PI-RADS], scores) compared with F-choline PET/mpMRI to detect Gleason ≥ 3+4 cancer. The per-lesion accuracy of systematic plus targeted biopsy for mpMRI alone was 67.8% (area under receiver-operating-characteristic curve [AUC], 0.73) for Likert 4-5 and 70.0% (AUC, 0.76) for PI-RADS 3-5. Several PET/MRI models incorporating F-choline with mpMRI data were investigated. The most promising model selected all high-risk disease on mpMRI (Likert 5 or PI-RADS 5) plus low- and intermediate-risk disease (Likert 4 or PI-RADS 3-4), with an elevated F-choline target-to-background ratio greater than 1.58 as positive for significant cancer. Using this approach, the accuracy on a per-lesion basis significantly improved to 88.9% for Likert (AUC, 0.90; < 0.001) and 91.1% for PI-RADS (AUC, 0.92; < 0.001). On a per-patient basis, the accuracy improved to 92.9% for Likert (AUC, 0.93; < 0.001) and to 91.1% for PI-RADS (AUC, 0.91; = 0.009). F-choline PET/mpMRI improved the identification of Gleason ≥ 3+4 prostate cancer compared with mpMRI, with the principal effect being improved risk stratification of intermediate-risk mpMRI lesions.